Biosynthesis of ZnO Nanoparticles from Aqueous Extract of Moringa Oleifera L.: Its Application as Antibacterial and Photocatalyst (Universitas Negeri Semarang, 2022)
ZnO nanoparticles were successfully synthesized by the biosynthesis method using water extract of Moringa leaf (Moringa oleifera L.) as a reducing agent and stabilizer as well as a capping agent. This study aimed to characterize ZnO nanoparticles and their application as antibacterial and photocatalyst. Characterization was carried out using Fourier Transform Infrared (FT-IR) Spectroscopy and X-Ray Diffraction (XRD). The biosynthesis ZnO nanoparticles have a hexagonal wurtzite phase with an average crystal size of 16.97 nm and a crystallinity level of 78.49%. Antibacterial activity of ZnO nanoparticles with concentrations of 3%, 6%, 9% resulted in an average inhibition zone of bacterial growth in S. aureus was 19.6 0.16; 21.8 0.33; 24.3 0.14 and in E.coli it is 9.87 0.2; 11.3 0.04; 11.57 0.06. The greater the concentration of ZnO nanoparticles, the larger the diameter of the inhibition zone. The result of photodegradation of methylene blue is greatest with variations in the mass of ZnO nanoparticles and the concentration of methylene blue is 95% with a nanoparticle mass of 120 mg, methylene blue concentration of 10 ppm, and an irradiation time of 150 minutes.